Autologous hematopoietic stem cell transplantation following alemtuzumab therapy in aggressive multiple sclerosis: A report of three cases. (June 2021) - Boffa, Giacomo; Sbragia, Elvira; Raiola, Anna Maria; Varaldo, Riccardo; Capello, Elisabetta; Gallo, Paolo; Granella, Franco; Mancardi, Gianluigi; Inglese, Matilde
The management of multiple sclerosis patients with persistent disease activity under alemtuzumab treatment is not established yet. Concerns have been raised on the safety of autologous haematopoietic stem cell transplantation (aHSCT) after alemtuzumab treatment because of the risk of serious infectious adverse events. We report short-term safety and efficacy data from three patients treated with aHSCT following alemtuzumab treatment. Early adverse events were consistent with expected transplant toxicities. All patients were free of disease activity at the last follow-up. Our data suggest that aHSCT can be considered as a rescue treatment strategy for MS patients with persistent disease activity during alemtuzumab treatment.